Implementasi Dana Zakat, Infaq, Dan Shadaqah Perspektif Hukum Ekonomi Islam (Penelitian di Baznas Kabupaten Garut ) - Abdillah, Syaik; Azzurri, Fikran Ashil (STAI Al Musaddadiyah Garut, 2022)
Zakat is an Islamic teaching with mandatory legal force established in the Quran, the Sunnah of the Prophet, and the consensus of scholars. Zakat is also alongside the obligation of prayer, as stated in the Quran in Surah Al-Baqarah verse 277. Based on information found by the researcher, there are instances of zakat distribution being directed only to specific parties, resulting in the favoritism of one group. This raises concerns regarding the lack of alignment with the principles of Islamic economic law in line with the objectives of Shariah maqasid. The formulation of the problem in this research is: How is the implementation of zakat, infaq, and sadaqah fund distribution in BAZNAS (National Amil Zakat Agency) Garut Regency? How is the implementation of zakat, infaq, and sadaqah fund distribution according to the perspective of Islamic economic law? From these research problem formulations, the objectives of this study are 1. To describe the implementation of zakat, infaq, and sadaqah fund distribution managed by BAZNAS Garut Regency. 2. To describe the implementation of zakat, infaq, and sadaqah fund distribution from the perspective of Islamic economic law. This research is classified as qualitative research using a descriptive approach. The results of this research indicate that the implementation of ZIS (Zakat, Infaq, and Sadaqah) fund distribution in BAZNAS Garut is rotated and distributed to those entitled to receive it according to appropriate eligibility criteria and procedures. Therefore, it can be concluded that from the perspective of Islamic economic law, the implementation is appropriate, but there is a need for improved socialization regarding distribution and more transparent information about distribution activities to the public so that those in need can be aware of it. Keywords: Islamic Economic Law, Zakat, Infaq, Sadaqah